CD95's deadly mission in the immune system - Krammer, Peter H. (Nature, 2000)
Apoptosis in the immune system is a fundamental process regulating lymphocyte maturation, receptor repertoire selection and homeostasis. Thus, death by apoptosis is as essential for the function of lymphocytes as growth and differentiation. This article focuses on death receptor-associated apoptosis and the role of CD95 (Apo-1/Fas)-mediated signalling in T-cell and B-cell development and during the course of an immune response. Gaining an insight into these processes improves our understanding of the pathogenesis of diseases such as cancer, autoimmunity and AIDS, and opens new approaches to rational treatment strategies.
Gesehen am 03.03.2021